The Kip Brothers - Verne, Jules, 1828-1905 (Book collections on Project MUSE., 2007)
Castaways on a barren island in the South Seas, Karl and Pieter Kip are rescued by the brig James Cook. After helping to quell an onboard mutiny, however, they suddenly find themselves accused and convicted of the captain's murder. In this story, one of his last Voyages Extraordinaires, Verne interweaves an exciting exploration of the South Pacific with a tale of judicial error reminiscent of the infamous Dreyfus Affair.